Analisis Penerimaan Aplikasi Salaman, Pelayanan Administrasi Kependudukan Digital Kota Bandung - Wargadinata, Ella Lesmanawaty'; Nawawi, Nawawi; Suratha, I Gede; Munawaroh, Nunung; RP Tendean, Noudy (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2025)
The Salaman application is an online population administration service in Bandung, launched at the end of 2018. The application developed rapidly during the COVID-19 period and is still maintained as a public service innovation to this day. The Salaman application is considered a good application, with complete features, accessible language, and good security, but why is this application not fully used by the residents of Bandung City? The research uses the basic theory of the TAM-Technology Acceptance model from Davis (1989). The research method uses kuantitativemethods, SEM statistical tests for quantitative, and the Nvivo program for qualitative, which are used as data analysis instruments. Data sources include primary data from questionnaires, interviews, observations, and secondary data from various official documents and research by the research focus. The analysis results show that users will receive the Salaman application because it has 1) benefits, 2) makes it easy, and 3) is interesting to use as a population service. All variables positively and significantly influence the acceptance and use of the Salaman application. All variables positively and significantly influence the acceptance and use of the Salaman application. However, the Salaman application has not been able to attract the majority of heads of families as digital immigrants because it is considered 1) complicated, 2) exclusive, 3) Limited services 4) Lack of dissemination 5) Technical Problems 6) Trust issue 7) Responsive 8) Capability. Suppose the Bandung City Government’s Disdukcapil office aims to transform Bandung into a digital city with entirely digitized population services. In that case, several strategic efforts are essential: 1) Providing training, mentoring, and incentives to prepare Bandung City residents for the Salaman Application, facilitating their transition into engaged smart city residents, 2)Minimizing conventional methods of innovation to expand the digital service market among Bandung City residents.3)Implementing comprehensive policy support and adopting a holistic approach to effectively prepare for the transformation of conventional population administration services into digital platforms.